A Straightforward Approach to Synthesize 7-Aminocephalosporanic Acid In Vivo in the Cephalosporin C Producer Acremonium chrysogenum - Xuemei Lin; Jan Lambertz; Tim A. Dahlmann; Marc M. Nowaczyk; Burghard König; Ulrich Kück (Journal of Fungi, 2022)
The pharmaceutical industry has developed various highly effective semi-synthetic cephalosporins, which are generated by modifying the side chains of the core molecule 7-aminocephalosporanic acid (7-ACA). In industrial productions, the 7-ACA nucleus is obtained in vitro from cephalosporin C (CPC) by chemical or enzymatic processes, which are waste intensive and associated with high production costs. Here, we used a transgenic in vivo approach to express bacterial genes for cephalosporin C acylase (CCA) in the CPC producer Acremonium chrysogenum. Western blot and mass spectrometry analyses verified that the heterologous enzymes are processed into α- and β-subunits in the fungal cell. Extensive HPLC analysis detected substrates and products of CCAs in both fungal mycelia and culture supernatants, with the highest amount of 7-ACA found in the latter. Using different incubation times, temperatures, and pH values, we explored the optimal conditions for the active bacterial acylase to convert CPC into 7-ACA in the culture supernatant. We calculated that the best transgenic fungal strains exhibit a one-step conversion rate of the bacterial acylase of 30%. Our findings can be considered a remarkable contribution to supporting future pharmaceutical manufacturing processes with reduced production costs.